Borrelia burgdorferi sensu lato in Russia and neighbouring countries: high incidence of mixed isolates - Postic, D; Korenberg, E; Gorelova, N; Kovalevski, Y V; Bellenger, E; Baranton, G (Research in microbiology, 1997)
A total of 365 isolates of Borrelia burgdorferi sensu lato from 12 major administrative territories of Russia (from St. Petersburg in the west to South Sakhalin in the east) and from the Czech Republic, Estonia, Lithuania, Byelorussia, Moldavia, Ukraine and Kirghizia were identified by analysis of restriction polymorphism of ribosomal rrf-rrl spacer amplicons. The isolates were obtained mainly from ixodes persulcatus and I. ricinus ticks. Other sources included small mammals, human patients and I. trianguliceps ticks. The results showed that B. garinii (two variants) together with B. afzelii circulated throughout the territories studied. The distribution of the variant NT29 of the species B. garinii, the most frequently isolated, was associated with that of I. persulcatus ticks. B. burgdorferi sensu stricto, and the species B. valaisiana and B. lusitaniae (formerly the genomospecies VS116 and PotiB2, respectively) were isolated only from I. ricinus ticks in the western part of the studied territories. None of these three species were found in 327 isolates from Russia where I. persulcatus is the most frequently distributed vector. This work also provides evidence for a high incidence of mixed Borrelia infections within vectors and hosts (9.3% of isolates were mixtures of Borrelia species). A detailed analysis of Borrelia species distribution over the territories studied is presented.
Keywords: Moldavsko; Ukraine; Molecular Probe Techniques; Borrelia burgdorferi komplex; klíšťata; Ticks; Ixodes; Litva; Kyrgyzstán; lidé; molekulární sondy - techniky; Humans; Lyme Disease; Rusko; Lithuania; Russia; Moldova; Kyrgyzstan; Bacteriological Techniques; Animals; Czech Republic; zvířata; DNA bakterií; Republic of Belarus; polymerázová řetězová reakce; lymeská nemoc; Borrelia; Polymerase Chain Reaction; klíště; Ukrajina; Estonia; Česká republika; DNA, Bacterial; Borrelia burgdorferi Group; Estonsko; bakteriologické techniky; Běloruská republika